(untitled) (Economic and Political Thought, 2019)
The proposed regulatory reform in Georgia introduces impact assessment tool as part of the legislative process. While the lawmaker is accountable to the public and has a general duty to justify their actions, the political nature of parliamentary procedures makes it difficult to formally scrutinise legislature. This paper looks into the argumentative strategy of constitutional adjudication to showcase that the Georgian Constitutional Court possesses appropriate analytical framework to move towards realisation of rationality review of legislation.